Low-fluence blue light-induced phosphorylation of Zmphot1 mediates the first positive phototropism. (3rd August 2019) - Suzuki, Hiromi; Koshiba, Tomokazu; Fujita, Chiharu; Yamauchi, Yoshio; Kimura, Taro; Isobe, Toshiaki; Sakai, Tatsuya; Taoka, Masato; Okamoto, Takashi
Abstract : Ser291 in Zmphot1 was identified as a low-fluence blue light-induced phosphorylation site that is crucial for the first positive phototropism. Abstract: Phototropin1 (phot1) perceives low- to high-fluence blue light stimuli and mediates both the first and second positive phototropisms. High-fluence blue light is known to induce autophosphorylation of phot1, leading to the second positive phototropism. However, the phosphorylation status of phot1 by low-fluence blue light that induces the first positive phototropism had not been observed. Here, we conducted a phosphoproteomic analysis of maize coleoptiles to investigate the fluence-dependent phosphorylation status of Zmphot1. High-fluence blue light induced phosphorylation of Zmphot1 at several sites. Notably, low-fluence blue light significantly increased the phosphorylation level of Ser291 in Zmphot1. Furthermore, Ser291-phosphorylated and Ser369Ser376-diphosphorylated peptides were found to be more abundant in the low-fluence blue light-irradiated sides than in the shaded sides of coleoptiles. The roles of these phosphorylation events in phototropism were explored by heterologous expression of ZmPHOT1 in the Arabidopsis thaliana phot1phot2 mutant. The first positive phototropism was restored in wild-type ZmPHOT1 -expressing plants; however, plants expressing S291A-ZmPHOT1 or S369AS376A-ZmPHOT1 showed significantly reduced complementation rates. All transgenic plants tested in this study exhibited a normal second positive phototropism. These findings provide the first indication that low-fluence blue light induces phosphorylation of Zmphot1 and that this induced phosphorylation is crucial for the first positive phototropism.